2003
DOI: 10.1152/ajpregu.00028.2003
|View full text |Cite
|
Sign up to set email alerts
|

Responses to GABA-A receptor blockade in the hypothalamic PVN are attenuated by local AT1 receptor antagonism

Abstract: (PVN) has been repeatedly shown to increase arterial blood pressure (ABP), heart rate (HR), and sympathetic nerve activity (SNA), but the mechanism(s) that underlies this response has not been determined. Here, we tested whether full expression of the response requires activation of local ANG II AT 1 receptors. ABP, HR, and renal SNA responses to PVN microinjection of bicuculline methobromide (BIC; 0.1 nmol) were recorded before and after microinjection of vehicle (saline); losartan (or L-158809), to block lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
63
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 39 publications
10
63
0
Order By: Relevance
“…In support of this hypothesis, we found that PVN administration of two AT1R antagonists, candesartan and valsartan, significantly decreased arterial BP in water-deprived rats. In contrast, AT1R blockade had little effect in waterreplete animals, in agreement with previous reports (12,49). Interestingly, the depressor response was slowly developing, reaching its nadir only after 15-20 min.…”
Section: Discussionsupporting
confidence: 92%
“…In support of this hypothesis, we found that PVN administration of two AT1R antagonists, candesartan and valsartan, significantly decreased arterial BP in water-deprived rats. In contrast, AT1R blockade had little effect in waterreplete animals, in agreement with previous reports (12,49). Interestingly, the depressor response was slowly developing, reaching its nadir only after 15-20 min.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous studies, 4,5,6,22 our data show that BMI microinjected into the PVN in rats infused with vehicle for 7 days significantly increases renal SNA, MAP, and HR. In contrast, rats infused with Ang II had significantly blunted responses.…”
Section: Discussionsupporting
confidence: 91%
“…Standard methods were used to record renal SNA. 4,17 Renal SNA responses to intravenous sodium nitroprusside and phenylephrine were used to assess the signal-to-noise ratio of each recording. Hematocrit was measured from venous blood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of receiving strong tonic inhibitory input (Chen and Toney 2003b;Chen et al 2003;Kenney et al 2003;Li et al 2006;Martin et al 1991), PVN neurons nevertheless do contribute to ongoing SNA. In anesthetized rats, for example, studies have shown that acute inhibition of PVN neuronal activity or blockade of excitatory inputs reduces ongoing renal SNA (RSNA) (Akine et al 2003;Allen 2002;Stocker et al 2004b, lumbar SNA , and ABP (Akine et al 2003;Allen 2002;Freeman and Brooks 2007;Stocker et al 2004b.…”
Section: Introductionmentioning
confidence: 99%